Effectiveness of Universal Design for Learning on Academic Engagement and Emotional Regulation of Students with Autism Spectrum Disorder (Equilibrium: Jurnal Pendidikan, 2026)
This study examines the effectiveness of Universal Design for Learning (UDL) implementation on academic engagement and emotional regulation of students with Autism Spectrum Disorder (ASD) in inclusive elementary schools. A quasi-experimental pretest–posttest design without a control group was employed. Eight students with ASD in inclusive classrooms were selected through purposive sampling. The UDL intervention was implemented over five weeks applying the principles of multiple means of engagement, representation, and action and expression. Data were collected using observational scales of academic engagement (adapted from Fredricks et al., 2019) and the Emotional Regulation Checklist (Shields & Cicchetti, 1997). Paired sample t-tests and Cohen's d effect size were used for analysis. Normality tests confirmed normal data distribution (p > .05). Significant improvements were found in academic engagement (t(7) = 5.21, p < .001, d = 1.20) and emotional regulation (t(7) = 4.87, p < .001, d = 1.10) following UDL implementation, both with large effect sizes. These findings suggest that UDL is effective in enhancing academic engagement and emotional regulation of students with ASD in inclusive settings, providing important implications for developing adaptive inclusive education practices in Indonesia.